Hyponatremia in Patients with Cirrhosis of Liver Admitted in the Medicine Ward of SBMCH- Study of 100 Cases - Mridha Mohammad Shahinuzzaman; Shahana Ahmed; Mamun Morshed; Mahadi Masud; Khandaker Aman Abdullah Najib (Asian Journal of Medical Research, 2025)
Background: Hyponatremia is a common and significant complication in cirrhosis, primarily resulting from altered fluid and electrolyte regulation. It is associated with advanced liver disease and poor clinical outcomes. This study aimed to assess the prevalence, clinical characteristics, and prognostic significance of hyponatremia in cirrhotic patients with ascites at Sher-E-Bangla Medical College Hospital (SBMCH), Barisal, Bangladesh. Objective: To evaluate the prevalence of hyponatremia in cirrhotic patients with ascites, its relationship with ascites severity, diuretic therapy, liver dysfunction markers, and its impact on clinical outcomes. Subjects and Methods: This hospital-based, cross-sectional study was conducted over six months (January to June 2012) at SBMCH, including 100 cirrhotic patients with ascites. Data were collected using a structured case record form, documenting demographics, clinical symptoms, biochemical parameters, and sodium levels. Diuretic therapy and ascites characteristics were recorded. Statistical analysis was performed using SPSS, with p-values ≤0.05 considered statistically significant. Results: Among the 100 patients studied, 56% had serum sodium concentrations ≤130 mmol/L, indicating a high prevalence of hyponatremia. Patients with lower sodium levels had more severe ascites, with 100% of those in the ≤130 mmol/L group presenting with refractory ascites. Diuretic therapy, primarily consisting of spironolactone and furosemide, was administered to 84% of the cohort. Serum albumin levels were significantly lower in patients with sodium concentrations ≤130 mmol/L. Additionally, the need for paracentesis was more frequent in patients with sodium ≤130 mmol/L, reflecting the greater severity of fluid retention in these individuals. Conclusion: Hyponatremia is prevalent in cirrhotic patients, especially those with refractory ascites, and is associated with more severe ascites, hypoalbuminemia, and worsened liver function. Effective management of hyponatremia is critical for improving outcomes in these patients. Further research is needed to explore the mechanisms behind hyponatremia and its impact on liver transplantation outcomes.